Identification of the Phytochemicals in Passiflora edulis f. edulis and Passiflora edulis f. flavicarpa - Poornima, Jeyasekaran; M., Deepa (INTI International University, 2022)
Phytochemicals are found abundantly in plants which are non-nutritive and bio active compounds that prevents the onset of degenerative diseases and protects the body by maintaining the health. The chemical constituents of food have the ability to protect and prevent the humans from degenerative diseases. The objective of this study is to identify the chemical components of two varieties of passion fruits Passiflora edulis f. edulis with Passiflora edulis f. flavicarpa available wildly in the Thandikudi hills, Tamil Nadu, India and compare the sensory attributes between the two varieties of the prepared squashes. High tech instrument the JASCO FTIR spectrophotometer (FTIR‐4600) was used to identify the chemical constituents in the fruits. The results showed the presence alkane, primary alcohol, aldehyde and aromatic compounds in the fruit pulp. The inferential statistical analysis of the sensory evaluation revealed that the panel members categorized the Passiflora edulis f. edulis squash to be more acceptable when compared to the Passiflora edulis f. flavicarpa squash in the 9 -point hedonic scale. Further this study can be extended on comparing the other varieties of passion fruits and make them a commercial product for marketing.